Systematic Literature Review: Rancang Bangun Image Digital Watermarking - Vira Kristianingrum; Muhammad Faishal; Agung Susilo Yuda Irawan (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2022)
Digital Image Watermarking is a technology used in information security applications such as protection of digital image content and copyright protection. Digital image watermarking is an interesting area of research because it protects multimedia data from unauthorized access. To design an efficient and robust digital image watermarking system, a balance must be maintained. In this Systematic Literature Review (SLR), we conduct a brief review of the literature on digital image watermarking on journal papers published from 2018. Watermarking algorithms can be classified based on different criteria. Depending on the particular application, the watermarking algorithm must meet certain requirements. The expected result of this research is to know what digital image watermarking is, what it is for and is it useful to do digital image watermarking.